Analysis of The Influence of Changing Land Area on The Value of Gross Regional Domestic Product (GRDP) (Case Study: Lampung Province) - Ratna Mustika Sari; Albertus Deliar; Andri Hernandi (Politeknik Negeri Batam, 2023)
Residents' activities will always use the land as a place to carry out activities which will affect the GRDP value. This study uses data on the GRDP values of Lampung Province in 2014–2021 obtained from BPS Lampung Province and uses land cover area data obtained from the classification results of Landsat 8 imagery for 2014–2021. The data analysis technique used in this study is correlation analysis and linear regression using panel data. The results of the correlation analysis found that the value of GRDP in total, GRDP in the agriculture, forestry, and fisheries sectors, GRDP in the processing industry sector, and GRDP in the construction sector all correlated with built-up land cover, for GRDP in the agriculture, forestry, and fisheries sectors, in addition to correlation with built-up land cover as well correlated with paddy field cover, and pond land. GRDP values that correlated with the land cover area were carried out by a linear regression analysis of panel data. The results of panel data linear regression calculations show that changes in the area of built-up land cover in Lampung Province do not affect the total value of GRDP, but the built-up land cover has a negative effect on GRDP in the agriculture, forestry, and fisheries sectors and a positive effect on GRDP in the processing industry sector and GRDP in the construction sector. The area covered by paddy fields and ponds has a positive effect on GRDP in the agriculture, forestry, and fisheries sectors. Keywords: Land Cover, GRDP, Panel Data Linear Regression, Correlation